Maternal obesity alters fatty acid oxidation, AMPK activity, and associated DNA methylation in mesenchymal stem cells from human infants - Kristen E. Boyle; Zachary W. Patinkin; Allison L.B. Shapiro; Carly Bader; Lauren Vanderlinden; Katerina Kechris; Rachel C. Janssen; Rebecca J. Ford; Brennan K. Smith; Gregory R. Steinberg; Elizabeth J. Davidson; Ivana V. Yang; et al. (Elsevier, 2017)
Objective: Infants born to mothers with obesity have greater adiposity, ectopic fat storage, and are at increased risk for childhood obesity and metabolic disease compared with infants of normal weight mothers, though the cellular mechanisms mediating these effects are unclear. Methods: We tested the hypothesis that human, umbilical cord-derived mesenchymal stem cells (MSCs) from infants born to obese (Ob-MSC) versus normal weight (NW-MSC) mothers demonstrate altered fatty acid metabolism consistent with adult obesity. In infant MSCs undergoing myogenesis in vitro, we measured cellular lipid metabolism and AMPK activity, AMPK activation in response to cellular nutrient stress, and MSC DNA methylation and mRNA content of genes related to oxidative metabolism. Results: We found that Ob-MSCs exhibit greater lipid accumulation, lower fatty acid oxidation (FAO), and dysregulation of AMPK activity when undergoing myogenesis in vitro. Further experiments revealed a clear phenotype distinction within the Ob-MSC group where more severe MSC metabolic perturbation corresponded to greater neonatal adiposity and umbilical cord blood insulin levels. Targeted analysis of DNA methylation array revealed Ob-MSC hypermethylation in genes regulating FAO (PRKAG2, ACC2, CPT1A, SDHC) and corresponding lower mRNA content of these genes. Moreover, MSC methylation was positively correlated with infant adiposity. Conclusions: These data suggest that greater infant adiposity is associated with suppressed AMPK activity and reduced lipid oxidation in MSCs from infants born to mothers with obesity and may be an important, early marker of underlying obesity risk.